500 patterns for woodworking, laser cutting, and general crafting : full-size plans - Arndt, Fred (Fox Chapel Publishing, 2024)
"The ultimate pattern book for laser cutters, the book is packed with 500 intricate patterns for the laser cutter. Inside you'll find QR codes for pattern downloads, expert advice on wood selection and finishing, as well as a gallery of inspirational pieces. Each fretwork style project can be easily stacked to save time and includes everything from traditional-looking baubles to more modern trees, reindeer, vehicles and more."--